Researching school-business and industry cooperation in an opportunity-deprived and less wealthy, disadvantaged sector of a specific community in the Western Cape : towards effective partnership : an exploratory study - Cicero, Jennesin Abraham (Centre for Educational Research, 2016)
Bibliography: pages 101-111.